Palestinian Dynamics of Self-Representation: Identity and Difference in Palestinian Nationalism - Jamal, Amal (Hagar: Studies in Society and Culture, 2003)
This paper deals with the dialectics of identity construction and self-representation in the Palestinian national movement. It demonstrates how some transformations regarding self-image have been transpiring among Palestinians. It is divided into two main parts: the first deals with the first three decades following the 1948 exile during which thousands of Palestinians found themselves out of their homeland. This new reality led many of them to conceptualize a monolithic self-image that was presented to the world. As a result of the surrounding political, economic and cultural circumstances, as well as internal dissatisfaction with the official self-image propagated by the national movement, Palestinian intellectuals began to draw new self-images. The differences in experience and the discontent with the self-image received by the world, have induced various Palestinians to begin constructing self-images that portray their benevolent and humane sides. This process, still ongoing, mirrors the growing differentiation among Palestinians and marks the contention of some Palestinian intellectuals with the masculinist image propagated by the leadership of the national movement.